Antenatal Care, Malaria Screening and Anopheles Breeding Habitat Identification as Risk Factor in Pregnant Women Timika, Papua: Antenatal Care, Malaria Screening and Anopheles Breeding Habitat Identification as Risk Factor in Pregnant Women Timika, Papua - Lusiyana, Novyan; Rochmah, Fitria Siwi Nur (Aspirator, 2024)
Pregnant women are vulnerable to malaria infection, especially in highly endemic regions. Malaria infection in pregnancy can cause fetal growth restrictions and increase the risk of maternal death. This study aimed to perform malaria screening as well as identify maternal and fetal development and environmental factors that contribute to malaria transmission. This was a cross-sectional design. The study was conducted from January to March 2024 at the Naena Muktipura health center, Mimika. Every pregnant woman who visited the health center for ANC was examined in terms of weight, blood pressure, mid-upper arm circumference, fetal heart rate, malaria screening, and larval mosquito surveillance around the house. Malaria screening was done using RDT (Rapid Diagnostic Test). The types of stagnant water were recorded; larvae and larval genus were identified. A total of 14 pregnant women had ANC (Ante natal care); there were 34 ANC examinations within three months. The results of the ANC examination showed that the mothers and fetuses were in normal condition. The compliance to ANC for the pregnant mothers in the first, second, and third trimester was 100%, 75% and 60%, respectively. In fact, 100% of the pregnant women were not infected with Plasmodium, but 6 out of 21 locations of stagnant water around the houses of these pregnant women were confirmed to contain Anopheles sp. larvae. All pregnant women were not infected with Plasmodium, but the house condition and the presence of stagnant water with confirmed Anopheles larvae caused a risk for malaria transmission.